Caracterização do módulo elástico por espectroscopia mecânica da liga Ti-13Nb-13Zr - Muñoz Chaves, Javier Andres (2009)
In the present time the titanium and their alloys are begin widely studied in the field of biomaterials because of its suitable mechanical properties such as low elastic modulus, excellent corrosion resistance and high biocompatibility. Recent studies are being focused on alloys free of toxic elements as Al and V, which are contained in the alloy Ti-6Al-4V that is alloy generally used in biomedical implants, since biocompatibility studies revealed adverse effects on body in long-term implants. Ti-13Nb-13Zr alloy (TNZ) is one of these new alloys and is part of the present study. Were analyzed two samples of TNZ whit changes in their final processing, begin this labeled by TNZ + WQ (sample heat treatment to 900oC and water quenching) and TNZ + WQ + 400oC/3h (sample TNZ + WQ whit subsequent aging treatment to 400oC for 3hours), in the condition as received. For study the effect of heat treatment on physical properties besides to eliminate the internal stresses in the material, these samples were submitted to additional heat treatment to 900oC/30min. Thus, measures X-ray diffraction (XRD) and scanning electron microscopy (SEM) revealed the presence of phases a and b of structure hexagonal compact (HCP) and body-centered cubic (BCC) respectively, with a microstructure martensitic, typical of this alloy. The sample TNZ + WQ, on condition as received, phase a presented as only phase, however, after heat treatment (900oC/30min) were observed precipitates of phase b besides changes in the microstructure and density. The sample TNZ + WQ +400oC/3h in the condition as received showed the presence of phases a and b as expected, since after the aging treatment phase b is present in the form of precipitates. After treatment were observed changes in the microstructure, begin obtained a martensitic microstructure better defined. Mechanical spectroscopy measurements were performed using: decay free elastometer (flexural mode) and inverted torsion pendulum type Kê (torsional mode), and the spectra of anelastic relaxation not revealed the presence of relaxation mechanisms due to interstitial or substitutional solute atoms. This behavior was attributed to the presence of zirconium in the alloy which affects the distribution of interstitial solutes in solid solution and decreases the Zr-O pairs, processes of relaxation are obtained only when the stoichiometric rate of oxygen is saturated. About elastic modulus of the samples, was showed that heat treatment to reduce internal stress resulted in an increase in elastic modulus of the samples which was attributable to the presence of phase b